The missing 'gator of Gumbo Limbo : an ecological mystery - George, Jean Craighead (New York, NY : HarperCollins, 1992)
Sixth-grader Liza K., one of five homeless people living in an unspoiled forest in southern Florida, searches for a missing alligator destined for official extermination and studies the delicate ecological balance keeping her outdoor home beautiful.
Keywords: Alligators; Wildlife conservation; Ecology; Homeless persons